THEORETICAL APPROACHES TO ASSESSING THE SUSTAINABLE DEVELOPMENT OF SMALL BUSINESSES (Web of Teachers: Inderscience Research, 2026)
The importance of small business in ensuring economic growth and sustainable development in the world economy is growing. This sector has a positive impact on solving such issues as strengthening the competitiveness of the economies of developed countries, introducing the achievements of scientific and technological progress into production, creating new jobs and increasing the income of the population. The article presents theoretical approaches to assessing the sustainable development of small business reviewed.